IMPACT OF DIMETHOATE ON TOTAL LEUCOCYTE COUNT IN BLOOD OF MICE - ALAM, MD. AFTAB; KUMAR, PANKAJ; ., RANJANA; MISHRA, A.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
The dimethoate is a commonly used organophosphorous group of insecticide. The exposure of different mammalian species including humans to this compound is well documented. The effect of low to moderatelevels of repeated exposures of adult mice only to dimethoate have been examined on total leucocyte (TLC) in order to avoid hormonal interference associated with oestrous cycle in female mice. Male Swiss aslbino mice in 3-4 months of age group were administered four oral dosages of dimethoate (1, 5, 10. and 20 ppm) in different group everyday for 60 days. Treated and untreated control animals were sacrificed on 5, 10, 15. 30. 45 and 60TH days of treatments. TLC in blood samples from both control and experimental groups were analyzed. TLC in blood samples from both control and experimental groups were analyzed. Dimethoate treatments significantly increased TLC, which was dependent upon dose and the duration of the treatments. A dose of 10 ppm optimally effective in inducing significant change in TLC. The increase in TLC and the dose of dimethoate were positively correlated.